Work Values and Workplace Spirituality on Employee Performance: A Study at LPMP Maluku Province - Petronela Sahetapy (UIN Sunan Gunung Djati, 2023)
Performance has become an actual issue in an organization because it is a key question to the success of an organization, both private and public. The focal point of the performance analyzed in this study is central employees who work in regional agencies. Work values and spirituality in the workplace can influence employee performance. This can be seen from the performance of employees at LPMP Maluku Province. This study analyzed the influence of work values and spirituality in the workplace on employee performance at LPMP Maluku Province. The research approach used in this study is quantitative, survey, and explanatory research. Participants in this study were LPMP Maluku employees totaling 94 people and saturated sampling. The analysis technique used multiple linear regression with the assistance of SPSS 20.00. The results showed that 1) work values have a positive and significant effect on employee performance, 2) spirituality in the workplace has a positive and significant effect on employee performance, and 3) work values and spirituality in the workplace have a positive and significant effect simultaneously on employee performance. The suggestions that can be found are LPMP Maluku Province to pay attention to the dimensions of work values and spirituality in the workplace in synergy and strive to improve continuously because it is proven to have an effect on employee performance.